2002
DOI: 10.1074/jbc.m209177200
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Novel Recombinant Myoglobin Fusion Protein Expression System to Characterize the Tissue Inhibitor of Metalloproteinase (TIMP)-4 and TIMP-2 C-terminal Domain and Tails by Mutagenesis

Abstract: Tissue inhibitor of metalloproteinase (TIMP)-4 binds pro-matrix metalloproteinase (MMP)-2 and efficiently inhibits MT1-MMP, but unlike TIMP-2 neither forms a trimolecular complex nor supports pro-MMP-2 activation. To investigate the structural and functional differences between these two TIMPs, the C-terminal domains (C-TIMP-4 and C-TIMP-2) were expressed independently from their N domains and mutations were introduced into the C-terminal tails. Myoglobin was used as a novel recombinant fusion protein partner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
(98 reference statements)
1
29
0
Order By: Relevance
“…However, despite its ability to bind pro-MMP-2 (24), albeit with lower affinity than TIMP-2 (25), TIMP-4 was unable to support pro-MMP-2 activation by MT3-(shown here), MT1-(22, 26), or MT2-MMP (23). A pro-MMP-2⅐TIMP-4 complex does not bind MT1-MMP (22), an inability that has been attributed to specific structural constrains in the C-terminal region of TIMP-4 (24,70,71). Although not examined in this study, the relative low affinity and the structural orientation of the pro-MMP-2⅐TIMP-4 complex may preclude formation of a ternary complex with MT3-MMP and therefore activation does not ensue.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, despite its ability to bind pro-MMP-2 (24), albeit with lower affinity than TIMP-2 (25), TIMP-4 was unable to support pro-MMP-2 activation by MT3-(shown here), MT1-(22, 26), or MT2-MMP (23). A pro-MMP-2⅐TIMP-4 complex does not bind MT1-MMP (22), an inability that has been attributed to specific structural constrains in the C-terminal region of TIMP-4 (24,70,71). Although not examined in this study, the relative low affinity and the structural orientation of the pro-MMP-2⅐TIMP-4 complex may preclude formation of a ternary complex with MT3-MMP and therefore activation does not ensue.…”
Section: Discussionmentioning
confidence: 82%
“…The binding affinity and conformation of the pro-MMP-2⅐TIMP-2 complex allows the N-terminal region of TIMP-2 to dock into the active site of MT1-MMP yielding trimolecular complexes either in solution (22) or on the cell surface (14). Because the C-terminal tail of TIMP-3 has a net charge of zero, based on amino acid sequence (70), it has been suggested that the interaction of TIMP-3 with the positively charged hemopexin-like domain of pro-MMP-2 may be further weakened (70). In addition, studies using gelatin affinity chromatography suggested a lower affinity of pro-MMP-2 for TIMP-3 when compared with TIMP-2 (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have focused on the importance of the C-terminal domain of TIMP-2 for pro-MMP-2 activation (15,16,28). The results show that the charged residues Glu in the unstructured tail of TIMP-2 are crucial for the activation process.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-4 also binds to pro-MMP-2 through the hemopexin-like domain (13); however, it is unable to promote the activation of the zymogen by MT1-MMP (14,24,28), although it is an excellent inhibitor of the latter. Recent mutagenesis studies by several groups have identified residues Glu 192 and Asp 193 of the C-terminal "tail" of TIMP-2 as the key residues for binding to pro-MMP-2 (15,16). The lack of these residues in the TIMP-4 C-terminal tail probably reduces the stability of complex formation with the hemopexin-like domain of pro-MMP-2 leading to the inability of TIMP-4 to promote activation of pro-MMP-2.…”
mentioning
confidence: 99%